The Cyclicality of the Stepping Stone Effect of Temporary Agency Employment - Elke Jutta Jahn; Michael Rosholm (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper investigates whether the stepping stone effect of temporary agency employment moves over the business cycle. Using German administrative data for the period 1985-2012 and an estimation framework based on the timing-events model, we construct a time series of in-treatment and post-treatment effects and estimate their relationship to the aggregate unemployment rate. We find evidence for a strong lock-in effect of temporary agency employment that is even more pronounced in tight labor markets. This suggests that firms do not use agency employment as a screening device when unemployment is low. Moreover, we find a noticeable countercyclical positive post-treatment effect indicating that workers might be able to activate networks established while being in treatment. We further document that the treatment effects are non-linear over the business cycle.
Keywords: J64; J40; C41; 330